Rekonstruksi Diskresi Dalam Penyelenggaraan Pemerintahan Daerah Suatu Kajian Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Junaidi, Muhammad; Sadono, Bambang (Jurnal Selat, 2018)
Understanding the discretion or freedom act in countries such laws Indonesia is still have a dilemma due to the position of discretion position as a form of a policy still understood in partial not only the organizers State but also law enforcement. This is what then cause contradiction in the implementation of the State. This study was conducted by the ultimate goal is to provide clarity of the position of the implementation of the discretion in the implementation of the area. In addition to the research also want to analyze the extent of Law No. 23 Year 2014 on the Government the set in the discretion as one of the instrument of public policy. Through the juridical normative this research is expected to see and examines the extent apply the norm and asas that was supposed to be built in the construction of discretion against the implementation of the area. The approach is then do analysis in qualitative with the support of the data secondary consisting of the primary law, the legal tertiary and its laws secondary. The repositioning of discretion in the implementation of local government should certainly put discretion as a manifestation of the whole of the regional administration. The hierarchy of laws and regulations that often become obstacles element in understanding the implementation of discretion needs to be straightened out in accordance with the framework guidelines that the hierarchy of the law only as an element of the means of production in favor of justice, while through politics which is a forerunner to the creation of the essence of the law which aims to achieve fairness, certainty and expediency.